METAFORA KONSEPTUAL DALAM LIRIK LAGU BERTEMA PANDEMI CORONA KARYA MUSISI INDONESIA: KAJIAN SEMANTIK KOGNITIF - Ida Rahmawati; Millatuz Zakiyah (Universitas Sanata Dharma, 2021)
ABSTRACTThis study aims to analyze the use of conceptual metaphors in song lyrics. Similar to poetry, the use of language in song lyrics often brings up metaphors or other language styles with specific purposes and different backgrounds. Based on this, this study discusses the use of Lakoff and Johnson's version of the metaphor in the lyrics of songs with the theme of the corona pandemic by Indonesian musicians. Data retrieval using the technique of listening, notes and documentation. The data that has been collected is then analyzed using Lakoff and Johnson's conceptual metaphor theory. From the results of the analysis, the researchers found 31 forms of metaphor based on the classification of conceptual metaphor types proposed by Lakoff and Johnson consisting of 15 data containing structural metaphors (structural metaphors), 4 data containing orientational metaphors, 9 data containing ontological metaphors and 3 data containing the conduit metaphor. The purpose of using the metaphor which describes the negative point of view of Indonesian musicians in seeing the corona virus outbreak is stated in the lyrics of the song with the hope that the song aims to warn the wider community to always be careful and obey health protocols because the corona virus is very dangerous.